#TITLE_ALTERNATIVE# - SAPUTRA (Nim:15111102) ;Prof. Dr. Hasanuddin Z. Abidin, M.Sc .,Teguh Purnama Sidiq, ST., MT., DOLLY
This study aimed to observe land subsidence in Jakarta using interferometric SAR (InSAR) in the year 2014-2015. The method used in this study is a literature review and processing of image data through a process of differential SAR interferometry. Data processing is done by application GMTSAR . Analysis of the results of each stage of data processing is done to ensure that the end of data processing is a good result. The final results of the processing of this data is a map of land subsidence. The data used in this study has the image captured by four epoch in one year. From the results obtained map data processing land subsidence in Jakarta shows a subsidence up to 55.7 mm at Jl. Situ Babakan, West Jakarta. The rate of the subsidence still shows a linear rate up to 57.1 mm per year.